Variability in the area, energy and time costs of wintering waders responding to disturbance. (10th August 2016) - Collop, Catherine; Stillman, Richard A.; Garbutt, Angus; Yates, Michael G.; Rispin, Ed; Yates, Tina
Abstract : Birds' responses to human disturbance are interesting due to their similarities to anti‐predator behaviour, and understanding this behaviour has practical applications for conservation management by informing measures such as buffer zones to protect priority species. To understand better the costs of disturbance and whether it will impact on population size, studies should quantify time‐related responses as well as the more commonly reported flight initiation distance (FID). Using waders wintering on an estuarine area, we experimentally disturbed foraging birds on the Wash Embayment, UK, by walking towards them and recording their responses (FID, alert time, time spent in flight, time taken to resume feeding, and total feeding time lost). We present data for 10 species of conservation concern: Curlew Numenius arquata, Oystercatcher Haematopus ostralegus, Bar‐tailed Godwit Limosa lapponica, Grey Plover Pluvialis squatarola, Redshank Tringa totanus, Knot Calidris canutus, Turnstone Arenaria interpres, Ringed Plover Charadrius hiaticula, Sanderling Calidris alba and Dunlin Calidris alpina . Larger species responded more strongly, response magnitude was greater under milder environmental conditions, and responses varied over both small and large spatial scales. The energetic costs of individual responses, however, were low relative to daily requirements and disturbance events were unlikely to be frequent enough to seriously limit foraging time. We suggest, therefore, that wintering wader populations on the Wash are not currently significantly negatively impacted by human disturbance during the intertidal foraging period. This is also likely to be the case at other estuarine sites with comparable access levels, visitor patterns, invertebrate food availability and environmental conditions.